Genome Editing Technologies for Crop Improvement - Zhao, Kaijun; Mishra, Rukmini; Joshi, Raj Kumar (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book compiles the relevant information related to genome editing tools and their roles in crop improvement. The book contains a brief introduction about various genome editing tools and their application in major crops. It discusses the genome editing approaches and the strategies used for genome editing in different crops. Some of the chapters cover the detailed methodology of sgRNA design, vector construction and transformation in different crops followed by data analysis. A few chapters focus on the applications of genome editing tools towards crop improvement. This book will be of particular interest to plant biologists working in the field of genome editing and crop breeders. It will provide valuable information and useful material for our readers' experimental work.
PART I: INTRODUCTION TO GENOME EDITING AND CROP IMPROVEMENT -- Chapter 1. Genome editing is revolutionizing crop improvement -- PART II: GENOME EDITING TOOLS AND APPROACHES -- Chapter 2. Genome editing tools for food security -- Chapter 3. CRISPR/Cas9 based multi-gene editing in crops -- Chapter 4. CRISPR/Cas9 tool kit for multiplex genome editing in crops -- Chapter 5. Plant genome editing mediated by CRISPR/Cas12a system -- Chapter 6. Genome editing in crops via homology-directed repair using a gemini-virus based CRISPR/Cas9 system -- Chapter 7. Targeted gene replacement in plants using CRISPR-Cas technology -- Chapter 8. Expanding the scope of base editing in crops using Cas9 variants -- Chapter 9. Plant precise genome editing using prime editors -- Chapter 10. Off-target effects of crop genome editing and its minimization -- PART III: GENOME EDITING TOWARDS CROP IMPROVEMENT -- Chapter 11. Genome editing towards rice improvement -- Chapter 12. Genome editing for wheat Improvement -- Chapter 13. Genome editing for maize Improvement -- Chapter 14. Genome editing for Sorghum improvement -- Chapter 15. Accelerating Cereal breeding for disease resistance through CRISPR/Cas9 mediated genome editing -- Chapter 16. Genome editing for Soybean improvement -- Chapter 17. Genome editing for improvement of oil seed crops -- Chapter 18. Genome editing for potato improvement -- Chapter 19. Genome editing for tomato improvement.
Keywords: Agriculture; Plant biotechnology; Plant genetics; Botanical chemistry; Biomaterials; Nucleic acids; Biology-Technique.; Agriculture; Plant Biotechnology; Plant Genetics; Plant Biochemistry; Nucleic Acid; Biological Techniques